Enzymatic Activity and Horizontal Gene Transfer of Heavy Metals and Antibiotic Resistant Proteus vulgaris from Hospital Wastewater: An Insight - Manzar Alam; Nilofer Bano; Tarun Kumar Upadhyay; Reem Binsuwaidan; Nawaf Alshammari; Amit Baran Sharangi; Radhey Shyam Kaushal; Mohd Saeed (Canadian Journal of Infectious Diseases and Medical Microbiology)
Globally, the issue of microbial resistance to medicines and heavy metals is getting worse. There are few reports or data available for Proteus vulgaris (P. vulgaris), particularly in India. This investigation intends to reveal the bacteria’s ability to transmit genes and their level of resistance as well. The wastewater samples were taken from several hospitals in Lucknow City, India, and examined for the presence of Gram-negative bacteria that were resistant to antibiotics and heavy metals. The microbial population count in different hospital wastewaters decreases with increasing concentrations of metal and antibiotics. Among all the examined metals, Ni and Zn had the highest viable counts, whereas Hg, Cd, and Co had the lowest viable counts. Penicillin, ampicillin, and amoxicillin, among the antibiotics, demonstrated higher viable counts, whereas tetracycline and erythromycin exhibited lower viable counts. The MIC values for the P. vulgaris isolates tested ranged from 50 to 16,00 μg/ml for each metal tested. The multiple metal resistance (MMR) index, which ranged from 0.04 to 0.50, showed diverse heavy metal resistance patterns in all P. vulgaris isolates (in the case of 2–7 metals in various combinations). All of the tested isolates had methicillin resistance, whereas the least number of isolates had ofloxacin, gentamycin, or neomycin resistance. The P. vulgaris isolates displayed multidrug resistance patterns (2–12 drugs) in various antibiotic combinations. The MAR indexes were shown to be between (0.02–0.7). From the total isolates, 98%, 84%, and 80% had urease, gelatinase, and amylase activity, whereas 68% and 56% displayed protease and beta-lactamase activity. Plasmids were present in all the selected resistant isolates and varied in size from 42.5 to 57.0 kb and molecular weight from 27.2 to 37.0 MD. The transmission of the antibiotic/metal resistance genes was evaluated between a total of 7 pairs of isolates. A higher transfer frequency (4.4 × 10−1) was observed among antibiotics, although a lower transfer frequency (1.0 × 10−2) was observed against metals in both the media from the entire site tested. According to exponential decay, the population of hospital wastewater declined in the following order across all sites: Site II > Site IV > Site III > Site I for antibiotics and site IV > site II > site I >site III for metal. Different metal and antibiotic concentrations have varying effects on the population. The metal-tolerant P. vulgaris from hospital wastewater was studied in the current study had multiple distinct patterns of antibiotic resistance. It could provide cutting-edge methods for treating infectious diseases, which are essential for managing and assessing the risks associated with hospital wastewater, especially in the case of P. vulgaris.